Effects of a reminiscence therapy-involved program on anxiety, depression, and the quality of life in cancer patients: a meta-analysis of randomized controlled trials - Sun, Xingliang; Su, Wenlian; Yin, Mengyue; Xia, Ling (Frontiers in Psychology, 2024)
Objective Reminiscence therapy is increasingly being utilized for cancer patients to address psychological pressure and enhance their quality of life. This meta-analysis aimed to comprehensively evaluate the effect of a reminiscence therapy-involved program (RTIP) on anxiety, depression, and quality of life in cancer patients. Methods A systematic literature search was conducted in the Web of Science, PubMed, Embase, and Cochrane Library databases until December 2023 to screen randomized control trials (RCTs) comparing the effect of RTIP and control care. Results A total of 16 RCTs published from 2013 to 2023 were included, with 1,963 cancer patients undergoing RTIP with or without control care (RTIP group, N = 984) or control care (control group, N = 979). The results showed the the anxiety score [standardized mean differences (SMD) = −0.539; 95% confidence interval (CI) = −0.700, −0.378; P < 0.001], anxiety rate [relative risk (RR) = 0.736; 95% CI: 0.627, 0.865; P < 0.001], depression score (SMD = −0.664; 95% CI: −0.967, −0.361; P < 0.001), and depression rate (RR = 0.632; 95% CI = 0.532, 0.750; P < 0.001) were significantly reduced in the RTIP group compared to the control group. Furthermore, overall quality of life was increased in the RTIP group than in the control group (SMD = 0.501; 95% CI: 0.314, 0.689; P < 0.001). In digestive system cancer patients, anxiety/depression scores and rates were reduced, and the overall quality of life was elevated in the RTIP group in comparison with the control group (all P < 0.050). The quality of evidence was generally high, with a low risk of bias in most studies and no publication bias in any outcomes (all P > 0.050). Conclusion RTIP attenuates anxiety and depression and improves the quality of life in cancer patients, benefitting their overall health condition. Systematic Review Registration This meta-analysis was registered at PROSPERO with registration number CRD42024563266.